Populism and legislative backsliding - Akirav, Osnat (Frontiers in Political Science, 2025)
IntroductionThis study presents a comprehensive set of measurements for assessing legislative backsliding and authoritarian populist rhetoric.MethodsI demonstrate the use of these measures by comparing the discussions involved in passing three Basic Laws in Israel. One was enacted in the 20th Knesset term, whereas the other two were passed during the current 25th Knesset that began in 2022.Results and discussionThe findings indicate more legislative backsliding in the 25th Knesset than in the 20th Knesset. The quality of the deliberative process was poorer, there was less respect for informal institutions, and there was more use of formal procedures to change previous behavioral norms during the 25th Knesset. In addition, the use of authoritarian populist rhetoric increased during this Knesset term and was used to justify and legitimize legislative backsliding.